Capital asset pricing model testing at Warsaw Stock Exchange: Are family businesses the remedy for economic recessions? - Jacek Lipiec (International Journal of Financial Studies, 2014)
In this article, we test the capital asset pricing model (CAPM) on the Warsaw Stock Exchange (WSE) by measuring the performance of two portfolios composed of construction firms: family-controlled and nonfamily controlled. These portfolios were selected from the WIG-Construction (WIG-Warszawski Indeks Gieldowy-Warsaw Stock Exchange Index). The performance of both portfolios was measured in the period from 2006 to 2012 with respect to three sub-periods: (1) pre-crisis period: 2006-2007; (2) crisis period: 2008-2009; and (3) post-crisis period: 2010-2012. This division was constructed in this way to find out how family firms performed in crisis times in relation to nonfamily firms. In addition, the construction portfolio was chosen due to its sensitivity to recessions. When an economy faces a downturn, construction firms are among the first to be exposed to risk. The performance was measured by using the capital asset pricing model with statistical inference. We find that public family firms significantly outperformed non-family peers in the crisis times.
Keywords: D21; G12; 330; CAPM; beta; portfolio return; Polish family firms; Warsaw Stock Exchange CAPM; beta; portfolio return; Polish family firms; Warsaw Stock Exchange